The moderating role of environmental factors between institutional isomorphic pressures and the adoption of IFRS for SMEs: application of SEM - Paul Muda; Kingsley Tornyeva; John MacCarthy (Cogent Business & Management, 2024)
The purpose of the study was to assess the effect of institutional isomorphic pressures on the adoption of IFRS for SMEs in Ghana. This study administered a questionnaire to collect primary data to assess the relationship between the variables. Multistage sampling methods were used to select the sample size as the true representative of the 16 regions of Ghana without bias. The study employed factor analysis, and structural equation model analysis to test the null hypotheses in this study. The results revealed that coercive isomorphic and mimetic isomorphic pressures significantly affect the adoption of IFRS for SMEs positively in Ghana. However, normative isomorphic pressure has no significant effect on the adoption of IFRS for SMEs in Ghana. Secondly, the result showed that environmental factors moderate or strengthen the insignificant relationship between normative isomorphic pressure and the adoption of IFRS for SMEs. The study recommends that the government should collaborate with the regulator (ICAG) to give financial accounting education to the SME owners and accounts personnel of SMEs who lack or requisite skills to adopt and implement IFRS for SMEs in Ghana. Secondly, the regulator should create a special window for accounts personnel of SMEs to become members of professional bodies.
Keywords: M40; M41; M48; 650; IFRS for SMEs; coercive pressure; normative pressure; mimetic pressure; isomorphic pressure